1999
DOI: 10.1073/pnas.96.2.628
|View full text |Cite
|
Sign up to set email alerts
|

Role of decay-accelerating factor in regulating complement activation on the erythrocyte surface as revealed by gene targeting

Abstract: Decay-accelerating factor (DAF) is a glycosylphosphatidylinositol (GPI)-anchored membrane protein that inhibits both the classical and the alternative pathways of complement activation. DAF has been studied extensively in humans under two clinical settings: when absent from the erythrocytes of paroxysmal nocturnal hemoglobinuria (PNH) patients, who suffer from complement-mediated hemolytic anemia, and in transgenic pigs expressing human DAF, which have been developed to help overcome complement-mediated hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 38 publications
4
141
1
1
Order By: Relevance
“…Thus, it has been hypothesized that Crry plays the dominant role in control of the C3 step of complement activation in the mouse, overwhelming the importance of DAF (Quigg et al, 1998a;Quigg and Holers, 1995). The fact that Daf1 knock-out mice are viable, fertile, and show no major abnormalities constitutively (Lin et al, 2001;Sun et al, 1999) has contributed to this view.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been hypothesized that Crry plays the dominant role in control of the C3 step of complement activation in the mouse, overwhelming the importance of DAF (Quigg et al, 1998a;Quigg and Holers, 1995). The fact that Daf1 knock-out mice are viable, fertile, and show no major abnormalities constitutively (Lin et al, 2001;Sun et al, 1999) has contributed to this view.…”
Section: Discussionmentioning
confidence: 99%
“…We found that EryPs expressed several surface antigens found on EryDs, including Ter119, 39 CD71, 39 CD24, 41 CD55, 42 and CD147. 44 Simultaneous analysis of Ter119 and CD71 by flow cytometry revealed a developmental progression for circulating EryPs reminiscent of that found for EryDs.…”
Section: Cell-surface Phenotype Of Maturing Primitive Erythroblastsmentioning
confidence: 92%
“…To characterize further the development of circulating EryP, we stained for 3 additional surface antigens that have been detected on definitive erythroid cells. The glycoproteins CD24, 55 CD55, 42 and CD147/Basigin 44 were strongly expressed on all circulating EryP/ GFP ϩ cells at the developmental stages examined (Table 3; Figure 4). The GFP Ϫ cells (presumed EryD) also expressed CD24, CD55, and CD147, as expected, at levels comparable to those measured for EryP/GFP ϩ cells.…”
Section: Growth Factor Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD55 knockout (CD55 Ϫ/Ϫ ) mice and CD59 knockout (CD59 Ϫ/Ϫ ) mice were generated as described previously (18,19). These mice were deficient in the widely distributed GPI-decay-accelerating factor gene and CD59a gene (20 -22), respectively.…”
Section: Animalsmentioning
confidence: 99%